How improvisation drives lean search: The moderating role of entrepreneurial team heterogeneity and environmental uncertainty - Huang, Bo; Song, Jianmin; Jing, Yanguo; Xie, Yi; Li, Yuyu (Frontiers in Psychology, 2022)
Although lean search is seen as an important action in lean startup, previous studies have less knowledge on how to realize it, especially in the face of the traditional plans cannot cope with sudden changes in the environment. To fill the research gap, this study investigates the effects of improvisation (exploitative, explorative, and ambidextrous improvisation) on lean search. Meanwhile, this research also discusses the moderating effects of entrepreneurial team heterogeneity and the environmental uncertainty to identify the boundary conditions of this relationship. Supported by the cross-sectional data from 203 Chinese startups, the results show that explorative and ambidextrous improvisation are positively associated with lean search. However, the effect of exploitative improvisation on lean search is unsupported. Additionally, technology uncertainty positively moderates the relationship between exploitative improvisation and lean search. Market uncertainty positively moderates the relationship between explorative improvisation and lean search. However, the entrepreneurial team heterogeneity negatively moderates the relationship between ambidextrous improvisation and lean search. These findings contribute to understanding how startups could conduct lean search under in a rapidly changing environment, which provides theoretical guidance for improving the success rate of startups.